Management strategies: reproduction - John F. Smith; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1995)
Despite the negative effects of milk production on some reproductive traits, calving intervals between high- and low-producing groups varied by only 9 days (414 vs 423). First-service conception rates were 8 percentage points greater in the low-producing group than in the high-producing group. However, the percentage of cows not yet inseminated that were more than 120 days in milk was 18 percentage points greater in the low- than highproducing herds. When Kansas dairy herds in the DHIA program are evaluated, the higher producing herds seem to have lower firstservice conception rates and more services per conception. However, managers of high-producing herds are doing a better job of servicing cows inseminated earlier in lactation and putting replacements into the milk string at a younger age. This occurs because managers of high-producing herds have reproductive records and heat detection programs that allow them to detect a higher percentage of the cows in heat before 120 days in milk. Fine tuning the reproductive management program also can improve the profitability of a dairy operation. The reproductive losses in high-producing herds are considerably less than those in lowproducing herds ($139 vs $203). There are no magic formulas in establishing a good reproductive program. Combining good records, diligent heat detection, and sound artificial insemination technique can increase the profitability of a dairy.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Management; Reproduction